Impulse Noise Parameter Assessment in a Batch Radio Channel - A. Yu. Bekkiev; V. A. Makoviy (Российский технологический журнал)
Modern radio communication means to provide safe data transmission due to adapting radio channel to the actual noise environment. It is impossible to conduct proper comparative tests on various radio stations offered by manufacturers and to compare objectively the results obtained in field without actual signal parameters and noise environment instrument inspection at the reception point. The paper considers tactical level radio communications system operation when jammed with powerful impulse noise of various nature. It suggests a device enabling to assess the main parameters of impulse noise, namely desired signal and additive noise mixture envelope effective value, impulse noise envelope effective value, impulse noise duty factor. To provide measurement independence from a specific realization of a decoder it is suggested to use the envelope of a signal received by a radio station. The developed device uses standard radio channel data batches as measuring signals and does not require changing radio channel or radio network algorithms and timing charts. A method to assess the effective value of desired signal envelope and additive noise mean-square value when the received signal involves impulse noise is suggested. The paper demonstrates that valid assessment of desired signal and additive noise mixture is possible in case of setting aside selection values affected by impulse noise. A device separating symbols affected by impulse noise from those that are not affected is suggested. Formulas that allow synthesizing the device operation algorithms are obtained. The structure chart of the measurer is developed; the algorithms used to assess measured parameters are given.